The Use of Virtual Surgical Planning in Total Facial Skeletal Reconstruction of Treacher Collins Syndrome: A Case Report. Issue 3 (September 2018) - Guo, Yifan; Lopez, Joseph; Yang, Robin; Macmillan, Alexandra; Dorafshar, Amir H.
Facial skeletal reconstruction of patients with severe Treacher Collins syndrome (TCS) requires correction of both midface and mandibular deficiencies. Implementing virtual surgical planning can provide an accurate three-dimensional analysis of craniofacial abnormalities, creating calvarial donors that match the anatomy of the desired malar augmentation and facilitating bimaxillary movements, positioning, and fixation in orthognathic surgery. We present a case of an 18-year-old patient with TCS, who underwent staged zygomaticomaxillary reconstruction and double-jaw osteotomy with sliding genioplasty, using computer-assisted surgical planning. Following these operations, the patient achieved not only improved facial harmony but also class I occlusion.